Satellite estimation of pCO2 and quantification of CO2 fluxes in lakes in the context of climate change - Ruixue Zhao; Zhidan Wen; Yingxin Shang; Ge Liu; Hui Tao; Chong Fang; Sijia Li; Xiangfei Yu; Qian Yang; Jiping Liu; Kaishan Song (Ecological Indicators)
The large increase of greenhouse gases in the atmosphere, especially carbon dioxide (CO2), is the main cause of global climate change. Studies show that the CO2 exchange processes in the lake switch between the carbon source and the carbon sink action, thus impacting the global carbon cycle. In this study, we matched the surface reflectance of Landsat satellite images with the sampling measured partial pressure of carbon dioxide (pCO2) data of northeast lakes from 2016 to 2021, and constructed the pCO2 remote sensing inversion model. The XGBoost model achieved the optimal combination of fitting accuracy and Root Mean Square Error (R2 = 0.86, RMSE = 148.73 μatm) and validation accuracy (R2 = 0.71, RMSE = 186.14 μatm). The model was applied to long-time series remote sensing images for pCO2 inversion analysis of the northeast lakes (area > 1 km2). Final results show that since 1985, the northeast lake average pCO2 change in a downward trend, until 2023, the annual average of pCO2 has been significantly reduced to 363.58 μatm, and small lakes of pCO2 values are higher, large lakes have relatively small pCO2 values. However, chlorophyll a, total suspended matter and turbidity enhanced the overall trend of pCO2, and the water temperature and transparency were negatively correlated with pCO2. With increasing water temperature, lake pCO2 usually decreases. This study speculated that temperature, water quality and lake biodiversity changes would affect the average pCO2 of northeast lakes. The results are important for a deeper understanding of lakes in the global carbon cycle and the process of climate change.